Evaluation of Camera Use to Prevent Crime in Commuter Parking Facilities within the Washington Metro Area Transit Authority (WMATA) Parking Facilities, 2004-2009 - La Vigne, Nancy ([Verlag nicht ermittelbar], 2015)
This study sought to identify what parking facility characteristics and management practices within the Washington Metro Transit Police (MTP) might create opportunities for crime, analyze those findings in relation to past crimes, and identify promising crime reduction strategies. The project consisted of three main research components: (1) identification of the magnitude of car crime in commuter parking facilities and possible strategies for prevention of such car crime; (2) identification and implementation of a crime prevention strategy; and (3) evaluation of the strategy's effectiveness. In partnership with the MTP staff, the research team created a blocked randomized experimental design involving 50 matched pairs of commuter parking facilities in which a combination of live and dummy digital cameras were deployed, along with accompanying signage, at the exits of one randomly selected facility from each pairing. After a period of 12 months following camera implementation, the research team analyzed the impact of the cameras on crime occurring in and around Metro's parking facilities.